Robust track based alignment of the ATLAS silicon detectors and assessing patron distribution uncertainties in drell-yan processes - Heinemann, F; Heinemann, Florian (2007)
The ATLAS Experiment is one of the four large detectors located at the Large Hadron Collider (LHC) at CERN in Geneva, Switzerland. In summer 2008, ATLAS is expected to start collecting data from proton-proton collisions at 14 TeV centre-of-mass energy. In the centre of the detector, the reconstruction of charged particle tracks is performed by silicon and drift tube based sub-detectors. In order to achieve the ATLAS physics goals the resolutions of the measured track parameters should not be degraded by more than 20% due to misalignment. Thus, the relative positions of the silicon detector elements have to be known to an accuracy of about 10 micrometers in the coordinate with the best measurement precision. This requirement can be achieved by track based alignment algorithms combined with measurements from hardware based alignment techniques. A robust track based alignment method based on track residual and overlap residual optimisation has been developed and implemented into the ATLAS offline software framework. The alignment algorithm has been used to align a test beam setup and also part of the final ATLAS detector using cosmic ray muons. Several simulation studies showed that the algorithm will be able to align the full detector with collision data. In addition to detector misalignments, limitations in the knowledge of the proton structure are going to affect physics discoveries at the LHC. Therefore, parton distribution uncertainties in high-mass Drell-Yan processes have been determined. This study includes the analysis of the forward-backward asymmetry. It has been performed on the level of next-to-leading order in both, Monte Carlo simulation using k-factors and parton distribution functions. This analysis is crucial for new physics searches with the ATLAS detector.